Housing as a Human Right within an Era of International Exceptionalism - Erin Elizabeth Davis (Constitutional Review, 2021)
The right to adequate housing is an internationally recognized human right, yet it has been incontrovertibly desecrated by a lack of recognition, disproportionately affecting vulnerable groups. Economic, social, and cultural rights have encountered many challenges in an ever-increasing era of international exceptionalism and challenges arise in the protection of these rights. The right to housing is achieved in two ways: as a normative right and as a derivative right encompassed within economic, social, and cultural rights. This article introduces: (1) the normative development of economic, social, and cultural rights as recognized human rights, and their regulatory implementation through international instruments; (2) the concept of individuals as right-holders and duty-bearers of economic, social, and cultural rights; (3) understanding how the restriction of the right to housing leads to the violation of other human rights, including (a) the right to life, (b) the right to freedom from discrimination, and (c) the right to humane treatment – and the types of vulnerable groups that face the most discrimination, such as indigenous persons and women; and (4) protection against forced evictions, through an examination of the jurisprudence of the Inter-American System, European Court of Human Rights, and African Court on Human and Peoples’ Rights.